Efficacy and safety of taxane plus ramucirumab for advanced gastric cancer after chemotherapy plus nivolumab - Toshihiko Matsumoto; Tatsuki Ikoma; Chinatsu Makiyama; Tomoyo Yasuda; Shogen Boku; Akio Nakasya; Nobuhiro Shibata; Hiroki Nagai; Takao Tsuduki; Yusuke Matsumoto; Hisateru Yasui; Reiji Higashi; et al. (Scientific Reports)
Abstract Background and purpose Taxane plus ramucirumab (RAM) is the standard second-line treatment for advanced gastric cancer (AGC). However, data on second-line therapy following first-line treatment with nivolumab remains limited. This study aimed to evaluate the efficacy, safety, and prognostic factors of taxane plus RAM in patients with advanced AGC who previously received chemotherapy plus nivolumab. Materials and methods We collected data from AGC patients at multiple institutions who received taxane plus RAM after failure of chemotherapy plus nivolumab. All patients received first-line chemotherapy with nivolumab before December 2022. Results In total, 51 patients received taxane plus RAM (41 received paclitaxel plus RAM, and ten received nab-paclitaxel plus RAM). The median age was 70 years (range 41–83), 30 (59%) patients were male, and 45 (89%) had PS 0/1. Fourteen patients (27%) had liver metastases, 30 (59%) had peritoneal dissemination, and 25 (49%) had ascites; 43 patients had measurable lesions, nine (21%) achieved a partial response, and 21 (49%) achieved stable disease. Median progression-free survival was 3.7 months (95% confidence interval (CI) 3.1–5.1) and median overall survival was 8.9 months (95% CI 6.3–11.6). Major adverse events of grade 3 or higher were neutropenia (41%), anemia (10%), febrile neutropenia (8%), proteinuria (6%), and infection (4%). Multivariate analysis showed that ascites was a poor prognostic factor for overall survival. Conclusion Taxane plus RAM was effective in patients with AGC who have received prior chemotherapy plus nivolumab. The presence of ascites may be a poor prognostic factor in patients receiving taxane plus RAM.